Cálculo de la transferencia de calor en estado transitorio para una probeta estandarizada para el ensayo Jominy (2021)
In heat treatments, usually, to determine the effectiveness of the procedure, variables such as temperature variation, time and cooling method are taken into account; variables that allow predicting an approximate result. This method is used to improve the properties of a material according to the desired characteristics and its application. For this reason, theories and strategies have been studied to know the heat transfer; such as finite differences, which solves heat equations by determining the temperature of the element at different points, depending on its location and interaction with the environment in exposure. In this way, the research work explains the calculation of the heat transfer in transient state, with determined variables, for the cooling process of the Jominy test specimen, where the steel is subjected to a quenching treatment with water. The equations were formulated in the Excel program, taking into account the properties of the metal and the medium, focusing on the convection coefficient and thermal conductivity; consequently, the temperature change over time was determined, as specified in the ASTM A255-20 standard. These results were compared with those of the ANSYS STUDENT R2 program, and the solution of the equations presented in the Python program, combining the mathematical logic with the programmer's codes.